Preschool children’s play in the natural environment – pedagogical aspects and learning opportunities - Damnjanović, Jasmina; Dedaj, Marta; Radlović Čubrilo, Danijela (Norma, 2026)
From a theoretical point of view, the paper discusses the pedagogical aspects of play, natural play environments, as well as current practices worldwide and in Serbia regarding the learning opportunities of preschool children through play in nature. It starts from the fact that in the domain of structuring spatial units as stimulating environments for play, various structures can be found outdoors, which should above all be a safe environment for children. Outdoor play spaces can be equipped with various materials, equipment and toys. When attention is focused on learning through play in a natural environment, with natural materials, stimulating spaces for children can be: a kindergarten yard, a park, a meadow, etc., with the supervision and support of a teacher, whether it is learning through open, extended or guided play. Examples of different contexts of children’s play and learning through play in nature are presented, with a special emphasis on the support of educators in play, based on the Foundations of the Preschool Education Program "Years of Ascent". The proposed possibilities for supporting educators in the construction of play in nature can contribute to efforts to ensure that children’s exploration takes place in a creative way and to encourage the development of learning dispositions.